(untitled) (PETITUM, 2023)
ABSTRACT: This research aims to: (1) analyzing legal sanctions against children-narcotics dealers in realizing the diversion process. (2) analyze efforts to enforce diversion on children-narcotics dealers in realizing the diversion process. The method of presenting data in this research was carried out using library research, which is method of collecting data by searching and reviewing library materials. The results of this research show that: (1) Legal sanctions against children who distribute drugs still consider child’s survival and growth and development. (2) The implementation of diversion at the level of investigation, prosecution and examination of children’s cases in court can be carried out on children who are distributing narcotics for the first time. To realize justice and benefit in providing legal sanctions for children who traffic in narcotics, the diversion policy for children who are criminals remains under government supervision and guidance to ensure that these children no longer repeat their actions. ABSTRAK: Penelitian bertujuan untuk: (1) menganalisis sanksi hukum terhadap anak pengedar narkotika dalam mewujudkan proses diversi. (2) Untuk menganalisis upaya pemberlakuan diversi terhadap anak pengedar narkotika dalam mewujudkan proses diversi. Metode penyajian data dalam penelitian ini dilakukan dengan studi pustaka, yaitu suatu cara pengumpulan data dengan melakukan penelusuran dan menelaah bahan pustaka. Hasil Penelitian ini menunjukkan bahwa: (1) Sanksi hukum terhadap anak yang mengedarkan narkoba tetap mempertimbangkan kelangsungan hidup dan tumbuh kembang Anak. (2) Pemberlakuan diversi baik pada tingkat penyidikan, penuntutan, dan pemeriksaan perkara Anak di pengadilan dapat dilakukan terhadap anak yang baru pertama kali mengedarkan narkotika. Untuk mewujudkan keadilan dan kemanfaatan teradap pemberian Sangsi Hukum Terhadap Anak Pengedar Narkotika maka kebijakan diversi terhadap anak pelaku pidana tetap berada dalam pengawasan dan pembinaan pemerintah demi memastikan bahwa anak tersebut sudah tidak lagi mengulangi perbuatannya.